Aspectos generales de la potestad regulatoria - Vinocour Fornieri, Marta María (2016)
The regulatory authority, even though it is meager, has permeated the Costa Rican society in more recent years. That is why it is important to indicate its constitutional basis and its origin for a better understanding of Regulatory Law. This article begins with the origins, characteristics and the legal nature of regulation. Also, it establishes the fundamental characteristics that economic regulation must have to work efficiently. Other countries such as the United States, Great Britain, France, Argentina, Brazil and Chile are also referenced for a comparison of the operation of regulatory systems.